ANALISA RENCANA PROSES DAN ESTIMASI WAKTU PEMESINAN SUPPORT FITTINGS DARI AIRBUS A380 - , ANGGIH ANDREAS TAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tight competition pushed the manufacturing industries to function effective and efficient ways. That goal can be achieved using CAD/CAM/CNC system. PT. Dirgantara Indonesia at the same way were using CATIA V5 R19 and VERICUT for CAD/CAM/CAE system. Parts were designed, analysed and modified so the optimum design could be achieved. Those parts are aircraft components i.e. Support Fittings for example. The aim of this study is to discuss of the process of Support Fittings Part fabrication using CATIA V5 R19 and VERICUT. At first, models were created with CATIA V5 R19 using solid modeling technique and then simulated with CAM features (toolpath, machining parameters and NC file). Analysis on the output of CATIA V5 R19 show a less accurate toolpaths specially in the corner radius. This draw back were then examinated with VERICUT. VERICUT has the ability to estimate machining time and other parameters. Results show that it need approximately 51.25 minutes to machine the Support Fittings Parts.